ANALISIS PENYESUAIANÂ PTKP SEBELUM DAN SESUDAH PMK. NO 162/PMK.011/2012 TERHADAP JUMLAH PENERIMAAN PAJAK DANÂ WAJIB PAJAK PPH 21 PADA KANWIL DJP JATIM 1 - DWI ANGGAR KUSUMA, HARSELA (Jurnal Akuntansi AKUNESA, 2016)
Non-taxable income is the minimum life standards are given to state taxpayers that cannot be contested by anyone. This research aims to know the differences rule change the adjustment of the non-taxable income which is set in the PMK No. 162/PMK. 011/2012 against the amount of tax receipt PPh 21 and taxpayer PPh 21. The study was backed by the rule change by the continuous Non-taxable income occur caused by slowing global economic growth. This research uses data collection method interviews and documentation. Technique of data analysis using statistical testing and analysis of quantitative descriptive. The results showed there is difference in the amount of tax revenue PPh 21 and there is no difference in Taxpayer PPh 21 before and after the establishment of PMK NO. 162/PMK. 011/2012.  Keywords: Non-taxable income, Tax Receipt PPh 21, Tax Payer PPh 21